The Afterlife of Sai Baba: Competing Visions of a Global Saint, by Karline McLain - Shah, Tushar (Religions of South Asia, 2019)
The Afterlife of Sai Baba: Competing Visions of a Global Saint, by Karline McLain. Seattle and London: University of Washington Press, 2016. xiv + 262 pp., 55 (hb), 30 (pb). ISBN 978-0-29599-551-9 (hb), 978-0-29574-433-9 (pb).